Groups, Algorithms and Programming (GAP) and the Nonabelian Tensor Square of Groups of Order 8q - Rashid, S; ., . (International Journal of Engineering and Technology, 2018)
In this paper, the software package Groups, Algorithms and Programming (GAP)   is used to verify the hand calculation of  the nonabelian tensor square for groups of order 8q, where q is an odd prime.